Метод підвищення енергетичної ефективності HQPSK сигналів - Бондарєв, А. П.; Максимів, І. П.; Максимюк, Т. А. (Видавництво Національного університету "Львівська політехніка", 2016)
Показано можливість зростання енергетичної ефективності систем коміркового зв’язку за рахунок зменшення порогового відношення сигнал/шум за заданої частоти появи бітової помилки, з використанням особливого типу квадратурної фазової модуляції (HQPSK) і модифікованого фазового детектора. Обидва методи мають і переваги, і недоліки. Комбінація цих двох методів теоретично може зменшити їх недоліки, роблячи їх вигіднішими, ніж наявні методи. With the development of cellular communications, the different problems of effective spectrum utilization to provide a high quality of service for large number of mobile users have been emerged. For the last years the development of wireless communications became a large scale, inducing developers of radiotechnic devices to find new solutions to the problem of effective utilization of the allocated spectrum and effective power maintenance. Many types of spectral-efficient modulation of radio signals and new protocols that enable efficient distribution of network traffic have been proposed so far. One of the key parameters that are used for channel efficiency estimation is signal-to-noise ratio (SNR): the higher SNR results in lower bit-error rate and vice versa. Dependence between bit-error rate and signal-to-noise ratio is the key characteristic of the communication channel and optimization of this characteristic is an important task for communication networks. This paper shows the possibility of reducing the signal-to-noise ratio while maintaining the required bit-error rate by using specific type of quadrature phase shift keying (HQPSK) complemented by modified phase detector. Both methods have their advantages and disadvantages. The combination of these two methods can theoretically reduce their cons while effectively exploiting their advantages. The feature of the first method lies in power saving approach, providing the use of only one quadrature component during signal modulation, while the second quadrature component is coded using additional frequency subcarriers. The second method allows detection of quadrature signals at high noise power condition. This benefit is achieved by implementation of specific narrowband filters into phase detector.
Method for increasing the energy efficiency of HQPSK signals
Keywords: HQPSK; енергетична ефективність; спектральна ефективність; фазовий детектор; відношення сигнал/шум; Matlab Simulink; HQPSK; power efficiency; spectrum efficient; phase detector; signal-to-noise ratio; Matlab Simulink